Peningkatan Keterampilan Menulis Rangkuman Bacaan Melalui Penerapan Cooperative Learning Tipe Circ Kelas Iii Sd Negeri 3 Wonogiri Tahun Pelajaran 2016/ 2017 - Asprilla, Lia; , Drs. Rubino Rubiyanto,M,Pd (2017)
Based on observation result at grade 3 SDN 3 Wonogiri, it was found that the problem on learning was the literature summary writing hadn't been optimal yet. It was because the teacher hadn't apply learning model which attract students' interest in summarizing the literature. Student's score on literature summarizing was still under the standard (KKM). So, an effort is needed to improve the low writing skill on literature summarizing by the application of Cooperative Learning Type CIRC for 3rd grader of SDN 3 Wonogiri. This research was aimed to know the quality of writing skill on literature summarizing from the first cycle until the last cycle, the improvement of writing skill on literature summarizing by the application of Cooperative Learning Type CIRC. This research is a qualitative and quantitative research. The method which was used for collecting the data was observation, interview, test, and documentation. The method which was used to guarantee the accuracy of the data was triangulation of the source and method. The result of this research showed that the data which was obtained on precycle reached 32.17%, cycle I reached 55.41%, and cycle II reached 90%. From the percentage of students' learning result on precycle, cycle I, and cycle II showed that the application of Cooperative Learning Type CIRC can improve students' writing skill on literature summarizing.